Die Donau ist die Form : Strom-Diskurse in Texten und Bildern des 19. Jahrhunderts - Király, Edit (2017)
The monography traces the complex relationships between political discourses on the Danube and the aestheticization of the river landscape. It shows the making of the idea of a united Danube region paralleled by the conception of the region as a treshold between the East and the West in the 19th century.